PERBANDINGAN PERILAKU KECEPATAN BERLEBIH PENGEMUDI MOBIL DAN SEPEDA MOTOR - Kardina Nawassa Setyo Ayuningtyas; Aine Kusumawati; Estiara Ellizar (Jurnal Infrastruktur, 2021)
Speeding is one of the main causes of road crash fatality. This research aims to compare speeding behavior between car drivers and motorcyclists in terms of speed limit knowledge, excessive speed, the reason for speeding, and recommendation. It was found that motorcyclists tend to have speed limit perception higher than the speed limit based on regulation and more often to do speeding compared to car drivers. Speeding on urban roads was more frequent compared to intercity road. The main reason for speeding is the desire to reach the destination faster and on time. Several recommendations to reduce the speeding behavior are to install a speed reduction facility on urban roads, to separat lanes for motorcycles and cars on intercity roads, and better law enforcement.